2020
DOI: 10.1186/s41927-020-00142-7
|View full text |Cite
|
Sign up to set email alerts
|

Room for improvement in non-pharmacological systemic sclerosis care? — a cross-sectional online survey of 650 patients

Abstract: Background/ objective To gain insight in the use of current systemic sclerosis (SSc) care provided by health professionals from the patient perspective. We focused on referral reasons, treatment goals, the alignment with unmet care needs, and outcome satisfaction. Methods Dutch SSc patients from 13 participating rheumatology departments were invited to complete an online survey. Descriptive statistics were used to describe current use of non-pharmacological care and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
(52 reference statements)
1
13
0
Order By: Relevance
“…In clinical practice, the HPR treatment offer varies, as well as the content of the treatments, and there is little evidence available regarding HPR treatment for SSc-induced fatigue, hand function loss and RP/DU thus far [ 17–19 ]. Although HPRs offer numerous treatments to satisfy the unmet care needs of patients with SSc, and these patients are satisfied with the content and results of HPR treatments, fatigue, hand function loss and RP are uncommon reasons for referral to HPRs [ 18 , 20 , 21 ]. In a previous study, we found that rheumatologists are reluctant to refer their patients to HPRs due to a poor overview of HPR treatment options and a lack of published evidence [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, the HPR treatment offer varies, as well as the content of the treatments, and there is little evidence available regarding HPR treatment for SSc-induced fatigue, hand function loss and RP/DU thus far [ 17–19 ]. Although HPRs offer numerous treatments to satisfy the unmet care needs of patients with SSc, and these patients are satisfied with the content and results of HPR treatments, fatigue, hand function loss and RP are uncommon reasons for referral to HPRs [ 18 , 20 , 21 ]. In a previous study, we found that rheumatologists are reluctant to refer their patients to HPRs due to a poor overview of HPR treatment options and a lack of published evidence [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is also the case for systemic sclerosis (SSc), a rare, chronic autoimmune disease with multiorgan involvement (5). Physical therapists are among the most frequently visited health professionals in SSc, with the proportion of SSc patients visiting a physical therapist during 1 year ranging between 37% and 58% (6)(7)(8)(9). In the literature, SSc patients have expressed the need for improvement of non-pharmacological care, including physical therapy (10,11).…”
mentioning
confidence: 99%
“…Thus, improving healthcare provider competencies in shared decision-making is a key target for effectively implementing integrated SSc care [ 63 , 64 ]. Stocker et al [ 17 ] highlighted the need for patient decision aids to foster more patient-focused communication and support high quality decisions that are both informed and aligned with patient needs, values and preferences. Furthermore, our study revealed that patients may feel strained by too much, untimely or frightening information and may therefore refuse certain tests, examinations or interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Congruently, our interview participants described ‘ relying on an accessible and trustworthy team ’ as a central theme relating to finding trusted, reliable professionals and peers for ongoing care and support. Several studies have revealed similar gaps in SSc care delivery (i.e., lack of structured multidisciplinary collaboration, inadequately organized follow-up, poor patient-provider relationships [ 17 , 59 , 66 68 ]. Despite the positive impact the chronic care model has demonstrated on disease outcomes, rare disease care models rarely test multi-component interventions (e.g., patient education, patient-held medical records, specialist nurse-led care) in providing coordinated, ongoing, complex care [ 32 , 69 ] and infrequently incorporate community-based resources [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation